A Gallium Hydride as an Oxidizing Agent: Direct Synthesis of IrV Complexes via Ga−H Bond Activation. Issue 66 (7th November 2017) - Caise, Alexa; Abdalla, Joseph A. B.; Tirfoin, Rémi; Edwards, Alison J.; Aldridge, Simon
Abstract: Reactions of the β‐diketiminate‐stabilized gallium dihydride (Nacnac) Dipp GaH2 with chelating Ir I bis(phosphine) precursors under an H2 atmosphere are shown to provide a simple route to Ir V complexes stabilized by strongly σ‐donating hydrides and the carbene‐like (Nacnac) Dipp Ga donor. Characterization of these systems as seven‐coordinate Ir V tetrahydride species is supported by single crystal X‐ray and neutron diffraction, and by T 1 NMR measurements. By contrast related systems featuring more sterically demanding (non‐chelating) ancillary ligands are better described in terms of a bis(hydride) dihydrogen [L3 Ir(H)2 (H2 )] + formulation and a formal Ir III oxidation state. Abstract : High‐five !: Reactions of (Nacnac) Dipp GaH2 with chelating Ir I bis(phosphine) precursors provide a simple route to Ir V complexes stabilized by strongly σ‐donating hydrides and the carbene‐like (Nacnac) Dipp Ga donor. Related systems featuring more sterically demanding ancillary ligands, by contrast, are better described in terms of a bis(hydride) dihydrogen [Ir(H)2 (H2 )] formulation and a formal Ir III oxidation state.